2021
DOI: 10.1038/s41598-021-85456-3
|View full text |Cite
|
Sign up to set email alerts
|

Streptococcus pneumoniae endophthalmitis: clinical settings, antibiotic susceptibility, and visual outcomes

Abstract: Streptococcus pneumoniae endophthalmitis is clinically more severe, more difficult to treat, and carry a higher risk of vision loss, evisceration, or enucleation. This study is to investigate the clinical settings, antibiotic susceptibility, and visual outcomes of S. pneumoniae endophthalmitis at a tertiary referral center in Taiwan. S. pneumoniae endophthalmitis was diagnosed in 38 eyes of 38 patients. The main clinical features were postcataract endophthalmitis (n = 13, 34%) and endophthalmitis associated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 16 publications
1
6
1
Order By: Relevance
“…The nonsusceptibility rates of penicillin in bacteremia and meningitis isolates (1.3% and 65.9%) were lower than in a study conducted in Beijing China (8.5% and 71.9%) [ 16 ]. Consistent with many studies [ 47 49 ], S. pneumoniae in the present study is generally sensitive to vancomycin, linezolid, and levofloxacin, with 100% susceptibility. Erythromycin, clarithromycin, and azithromycin are the three most widely used macrolide antibiotics in the clinic.…”
Section: Discussionsupporting
confidence: 92%
“…The nonsusceptibility rates of penicillin in bacteremia and meningitis isolates (1.3% and 65.9%) were lower than in a study conducted in Beijing China (8.5% and 71.9%) [ 16 ]. Consistent with many studies [ 47 49 ], S. pneumoniae in the present study is generally sensitive to vancomycin, linezolid, and levofloxacin, with 100% susceptibility. Erythromycin, clarithromycin, and azithromycin are the three most widely used macrolide antibiotics in the clinic.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, it has been reported that the total carrying rate of S. pneumoniae in children is up to 17.8% (14). Patients with IPD are at risk of insomnia, hearing impairment, language and mental developmental delays (15)(16)(17), and even septic shock and death in severe cases (18). For children, delayed treatment of IPD can increase the risk of septic shock and mechanical ventilation by 4.58 times and 2.7 times, respectively, and the risk of death by nearly 40 times (19).…”
Section: Discussionmentioning
confidence: 99%
“…S. pneumoniae are the most commonly isolated streptococci from ocular infections such as conjunctivitis, endogenous and exogenous endophthalmitis, and keratitis [ 156 , 157 ]. S. pneumoniae is also the most common cause of bacterial keratitis in low-income countries [ 158 ].…”
Section: Gram-positive Ocular Pathogensmentioning
confidence: 99%
“…Among keratitis isolates, S. pneumoniae has been reported to have been isolated in 2% to 46.80% of cases ( Table 4 ). In cases of endophthalmitis, even with prompt treatment, there is a high risk of profound vision loss and enucleation or evisceration in eyes infected with S. pneumoniae [ 156 , 157 ]. Chen et al [ 157 ] reported that of 38 cases of S. pneumoniae endophthalmitis, 84% resulted in light perception to no light perception, and 26% underwent evisceration or enucleation.…”
Section: Gram-positive Ocular Pathogensmentioning
confidence: 99%
See 1 more Smart Citation